Do Narcotic Use, Physical Therapy Location, or Payer Type Predict Patient-Reported Outcomes After Anterior Cruciate Ligament Reconstruction?. Issue 4 (22nd April 2021) - ; Karnuta, Jaret M.; Dalton, Sarah; Bena, James; Farrow, Lutul D.; Featherall, Joseph; Jones, Morgan H.; Miniaci, Anthony A.; Parker, Richard D.; Rosneck, James T.; Saluan, Paul; Strnad, Greg; et al.
Background: Opioid use and public insurance have been correlated with worse outcomes in a number of orthopaedic surgeries. These factors have not been investigated with anterior cruciate ligament reconstruction (ACLR). Purpose/Hypothesis: To evaluate if narcotic use, physical therapy location, and insurance type are predictors of patient-reported outcomes after ACLR. It was hypothesized that at 1 year postsurgically, increased postoperative narcotic use would be associated with worse outcomes, physical therapy obtained within the authors' integrated health care system would lead to better outcomes, and public insurance would lead to worse outcomes and athletic activity. Study Design: Cohort study; Level of evidence, 2. Methods: All patients undergoing unilateral, primary ACLR between January 2015 and February 2016 at a large health system were enrolled in a standard-of-care prospective cohort. Knee injury and Osteoarthritis Score (KOOS) and the Hospital for Special Surgery Pediatric–Functional Activity Brief Scale (HSS Pedi-FABS) were collected before surgery and at 1 year postoperatively. Concomitant knee pathology was assessed arthroscopically and electronically captured. Patient records were analyzed to determine physical therapy location, insurance status, and narcotic use. Multivariable regression analyses were used to identify significant predictors of the KOOS and HSS Pedi-FABS score. Results: A total of 258 patients were included in the analysis (mean age, 25.8; 51.2% women). In multivariable regression analysis, narcotic use, physical therapy location, and insurance type were not independent predictors of any KOOS subscales. Public insurance was associated with a lower HSS Pedi-FABS score (–4.551, P = .047) in multivariable analysis. Narcotic use or physical therapy location was not associated with the HSS Pedi-FABS score. Conclusion: Increased narcotic use surrounding surgery, physical therapy location within the authors' health care system, and public versus private insurance were not associated with disease-specific KOOS subscale scores. Patients with public insurance had worse HSS Pedi-FABS activity scores compared with patients with private insurance, but neither narcotic use nor physical therapy location was associated with activity scores. Physical therapy location did not influence outcomes, suggesting that patients be given a choice in the location they received physical therapy (as long as a standardized protocol is followed) to maximize compliance.